2014
DOI: 10.4314/joafss.v11i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield, Nutrient Composition and Nutritive Quality of Silage Produced from Maize-Lablab Mixture

Abstract: Trials were conducted at the Teaching and Research farm, UNAAB in 2008 and 2009 to evaluate the effect of undersowing Lablab (Lablab purpureus cv. Rongai)in maize on grain yield, and to evaluate the nutritive quality of the silage in the dry season using calves.A 2ha piece of land was used for the experiment. In both years, maize was undersown with Lablab two weeks after planting (WAP)the maize. At harvest (10WAP), fresh weights and number of cobs, shelling percentage and weight of 1000grains of maize were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Maize-common bean mixture cropping had higher CPY than sole maize. This result was consistent with that of Amole et al [43], who reported that CPY increased in maize intercropped with climbing bean and lablab bean forages compared with monoculture maize.…”
Section: Resultssupporting
confidence: 93%
“…Maize-common bean mixture cropping had higher CPY than sole maize. This result was consistent with that of Amole et al [43], who reported that CPY increased in maize intercropped with climbing bean and lablab bean forages compared with monoculture maize.…”
Section: Resultssupporting
confidence: 93%
“…: biomass production efficiency, animal production efficiency and CH 4 emission reduction efficiency, with 1% level of significance along with benefit to cost efficiency which was correlated with maize index at 5% level of significance. [14]. The fact is, sometimes it is unable to achieve comparable rates of LWG using maize as sole; according to Aston and Tayler [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, legume materials are not easy to ensile because of their high buffering capacity (BC) and low level of water-soluble carbohydrate (WSC) [5]. Therefore, protein-rich legume and high-energy maize silage could be ensiled to upgrade nutrient composition [6]. Dairy farming, small ruminant farming, and commercial animal farming prefer maize silage as a rich nutritional source for enhanced production.…”
Section: Introductionmentioning
confidence: 99%